New registrations in Swedish beef cattle breeding - with focus on temperament and cow weight - Broström, Linn (2013)
In today’s genetic evaluation of Swedish beef cattle, mainly traits that are directly related to productivity are measured. However, other traits, such as temperament and mature cow weight affect the economy of the farmer, as well as the welfare of the animals. This thesis evaluates possible ways of measuring new traits, with focus on temperament and mature weight of suckler cows. The goal is to examine the possible benefits of including these traits in the Swedish breeding scheme. To achieve this, studies of literature, analyses of data and qualitative interviews with farmers have been conducted. Analyses of literature and data showed that recordings of temperament and mature weight can be performed during Swedish conditions. Data of Swedish farms showed that temperament scores were affected by breed, year and season, with the highest number of inferior temperament scores recorded around calving. Mature cow weights for Angus, Simmental and crossbreds were 700 to 820 kg, which is higher than figures stated in international literature. Effects of breed could not be observed for cow weight, which is contrary to findings in literature. To achieve a higher interest for breeding values, it is suggested to include new recordings, such as temperament, longevity and fertility, since it would capture the interests of the farmers and their breeding goals better. By including temperament during handling and aggressive behaviour around calving in the genetic evaluation, the safety for workers, animal welfare, productivity and economics at the Swedish farms could be improved. It is however not recommended to include mature cow weight in the genetic evaluation at present, due to lack of interest and thereof given benefits by inclusion of the trait. Although, the knowledge of the cows’ weights amongst farmers needs to be improved. In the future, this new information could be used to improve the Swedish beef recording scheme for a more efficient production.